Evaluation of a complex integrated, cross-sectoral psycho-oncological care program (isPO): a mixed-methods study protocol. Issue 3 (9th March 2020) - Jenniches, Imke; Lemmen, Clarissa; Cwik, Jan Christopher; Kusch, Michael; Labouvie, Hildegard; Scholten, Nadine; Gerlach, Alexander; Stock, Stephanie; Samel, Christina; Hagemeier, Anna; Hellmich, Martin; Haas, Peter; et al.
Abstract : Introduction: International standards of care require the complete integration of psycho-oncological care into biomedical cancer treatment. The structured integrated, cross-sectoral psycho-oncological programme 'isPO' is aiming to ensure a provision of care in inpatient and outpatient settings according to a stepped-care approach. Up to now, psycho-oncological care is missing regulated and standardised processes to demonstrate the effectiveness. This study protocol describes the process and outcome evaluation that is conducted, along with the isPO study. The programme evaluation is aiming to proof effectiveness, explain potential discrepancies between expected and observed outcomes. Additionally, provide insight into the implementation process, as well as contextual factors that might promote or inhibit the dissemination and implementation of the stepped care programme will be gained. In addition to these measures, a cost–consequence analysis will provide further evidence aimed at integrating psycho-oncological care into primary healthcare. Methods and analysis: The evaluation concept is based on a tripartite strategy consisting of a prospective, formative and summative evaluation. To capture all determinants, a concurrent mixed-method design is applied comprising qualitative (interviews and focus groups) and quantitative (standardised questionnaires) surveys of patients and healthcare providers. In addition, analysis of the psycho-oncological care data (isPO care data) and statutory health insurance claims data will be conducted. Primary and secondary data will complement one another (data linkage) to obtain a more comprehensive picture of the effectiveness and implementation of the complex intervention within the isPO study. Ethics and dissemination: The study has been approved by the ethics committee of the Medical Faculty of the University of Cologne. For all collected data, the relevant national and European data protection regulations will be considered. All personal identifiers (eg, name, date of birth) will be pseudonymised. Dissemination strategies include annual reports as well as quality workshops for the organisations, the presentation of results in publications and on conferences, and public relations. Trial registration number: DRKS00015326; Pre-results.